2011
DOI: 10.1590/s0100-204x2011000600007
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade, eficiência de uso da água e qualidade tecnológica de cana‑de‑açúcar submetida a diferentes regimes hídricos

Abstract: Resumo -O objetivo deste trabalho foi avaliar a produtividade de colmos e de açúcar, a eficiência de uso da água e os atributos tecnológicos de cinco variedades de cana-de-açúcar de maturação precoce e seis de maturação média à tardia, submetidas ao regime de sequeiro (1.141,4 mm) e à irrigação plena (1.396,6 mm). Utilizou-se o delineamento experimental de blocos ao acaso, com quatro repetições. A produtividade de colmos das variedades RB92579, RB72454 e SP81-3250 apresentou ganhos superiores a 180%, com uso d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
3
28

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 25 publications
3
28
3
28
Order By: Relevance
“…In percent terms, the mean TWD applied in the WS regime (1,510 mm) was only 24.4% higher than that applied in the WD regime (1,213.7 mm). These TWD values were lower than those recommended for 12-month-old sugarcane (1,500 to 2,000 mm) (Silva et al, 2014), a reflex of the better water application efficiency of the subsurface drip irrigation (Oliveira et al, 2011).…”
Section: Resultscontrasting
confidence: 62%
See 3 more Smart Citations
“…In percent terms, the mean TWD applied in the WS regime (1,510 mm) was only 24.4% higher than that applied in the WD regime (1,213.7 mm). These TWD values were lower than those recommended for 12-month-old sugarcane (1,500 to 2,000 mm) (Silva et al, 2014), a reflex of the better water application efficiency of the subsurface drip irrigation (Oliveira et al, 2011).…”
Section: Resultscontrasting
confidence: 62%
“…The joint analysis of the TCH data revealed that there was no significant interaction (p > 0.05) between the periods, water regimes and cultivars, indicating that the interannual variability of the imposed WRs was not able to promote alteration in the productive performance of the evaluated cultivars (Gava et al, 2011;Oliveira et al, 2011). The TCH of the cultivars showed significant interaction (p < 0.05) of periods versus water regimes (Figure 2A), periods versus cultivars ( Figure 2B) and water regimes versus cultivars ( Figure 2C), a reflex of the different application of the WRs in each cropping season.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Unlike this experiment, Oliveira et al (2011) observed increasing WP values when the crop was fully irrigated. These authors investigated eleven different sugarcane varieties and observed a water-use efficiency of 7.01 kg m -3 in rainfed and of 14.03 kg m -3 irrigated plants.…”
Section: Resultscontrasting
confidence: 60%